SPECTROSCOPIC MONITORING OF THE B[E] OBJECTS FSCMA AND MOCAM - Kuratova, A. K.; Miroshnichenko, A. S.; Zharikov, S. V.; Manset, N.; Khokhlov, S. A.; Raj, A.; Kusakin, A. V.; Reva, I. V.; Kokumbaeva, R. I.; Usenko, I. A.; Knyazev, A. Y. (Одеські астрономічні публікації, 2019)
Objects with the B[e] phenomenon exhibit permitted and forbidden emission lines due to the presence of circumstellar ionized gas and large infrared excesses due to processing of the stellar radiation by circumstellar dust. There are five groups of stars that show this phenomenon (pre-main-sequence Herbig Ae/Be stars, symbiotic systems, proto-planetary nebulae, some supergiant, and FS CMa type objects). The latter group is the most recently discovered and the least explored. The leading hypothesis about the group nature implies that they are mostly intermediate-mass binary sys- tems, whose circumstellar medium was created during a strong mass-transfer phase due to a Roche lobe overflow of the more massive star in the system. We have been conducting a large program of spectroscopic and photometric observations of many objects and candidates to this group. The current report is devoted to the preliminary results of our ongoing study of two objects with similar underlying early B-type stars, FS CMa (the group prototype) and MO Cam. The objects show different emission-line profiles and infrared excesses which are most likely due to different tilt angles of their non-spherical envelopes with respect to the line of sight. Variability of spectral lines is discussed here.